2004
DOI: 10.1162/15353500200404100
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescently Labeled Adenovirus with pIX-EGFP for Vector Detection

Abstract: Adenoviruses are extensively studied in terms of their use as gene therapy vectors and pathogenesis. These vectors have been targeted on both transcriptional and transductional levels to achieve cell-specific gene delivery. Current detection strategies, including reporter gene expression, viral component detection, and vector labeling with fluorophores, have been applied to analyze adenoviral vectors; however, these methods are inadequate for assessing transductional targeting. As an alternative to conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 40 publications
2
58
3
Order By: Relevance
“…This experiment demonstrated an increased number of Ad particles in the lungs of transgenic mice. 16 In the present study, we further confirmed the findings of both Tallone and our laboratory by demonstrating an increased expression of luciferase in lungs of hCAR mice compared to wild-type mice, after systemic administration of AdCMVLuc. Futhermore, gene expression in livers of hCAR mice was reduced compared to wild-type mice, possibly because of increased sequestration of Ad particles in the lung vasculature after tail vein injection.…”
Section: Discussionsupporting
confidence: 91%
“…This experiment demonstrated an increased number of Ad particles in the lungs of transgenic mice. 16 In the present study, we further confirmed the findings of both Tallone and our laboratory by demonstrating an increased expression of luciferase in lungs of hCAR mice compared to wild-type mice, after systemic administration of AdCMVLuc. Futhermore, gene expression in livers of hCAR mice was reduced compared to wild-type mice, possibly because of increased sequestration of Ad particles in the lung vasculature after tail vein injection.…”
Section: Discussionsupporting
confidence: 91%
“…Besides its role as a structural protein, it is a transcriptional activator (Rosa-Calatrava et al, 2001;Sargent et al, 2004a) and reorganizes promyelocytic leukaemia (PML) nuclear bodies (Rosa-Calatrava et al, 2003) (reviewed by Parks, 2005). Protein IX has been extensively studied as a platform to express foreign peptides on the surface of the capsid (Dmitriev et al, 2002;Le et al, 2004;Li et al, 2005;Meulenbroek et al, 2004;Vellinga et al, 2004Vellinga et al, , 2007. Since protein IX has been so well characterized, we selected it as a fusion partner to test whether 2A sequences could be used to express foreign genes in adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the presence of the pIX-eGPF fusion in purified Ad virions did not appreciably decrease virus viability or capsid stability, and has allowed monitoring of Ad localization in vitro and in vivo. 132,133 Further, other Ad vectors harboring complex ligands at the pIX locale have been reported. [134][135][136] As a whole, these studies have established pIX as a highly relevant capsid locale marked by the highest structural compatibility, with diverse targeting and imaging ligands observed to date.…”
Section: Adenovirus Targeting Via Genetic Modification: Other Capsid mentioning
confidence: 99%